Indicators of sarcopenia and their relation to intrinsic and extrinsic factors relating to falls among active elderly women - Liliana Laura Rossetin; Elisangela Valevein Rodrigues; Luiza Herminia Gallo; Darla Silvério Macedo; Maria Eliana Madalozzo Schieferdecker; Vitor Last Pintarelli; Estela Iraci Rabito; Anna Raquel Silveira Gomes (Revista Brasileira de Geriatria e Gerontologia)
Abstract Introduction: Musculoskeletal aging can impair functional performance increasing the risk of falls. Objective: To analyze the correlation between sarcopenia and the intrinsic and extrinsic factors involved in falls among community-dwelling elderly women. Method: A cross-sectional study evaluated the number of falls of 85 active community-dwelling elderly women in the previous year and then divided them into two groups: non-fallers (n=61) and fallers (n=24). The sarcopenia indicators assessed were gait speed (GS, 10m); handgrip strength (HS); calf circumference; appendicular muscle mass index (DXA). Intrinsic factors: Mental State Examination (MSE); visual acuity; depression (GDS-30); hip , knee (Lequesne) and ankle/foot (FAOS) pain/function; vestibular function (Fukuda test); functional mobility and risk of falls (TUG); power (sitting and standing five times); gait (treadmill); fear of falling (FES-I-Brazil). Extrinsic factors: risk/security features in homes. The independent t test was applied for comparisons between groups and the Pearson and Spearman tests were used for correlations (p<0.05). Results: There was a moderate correlation between HS and GS in non-fallers (r=0.47; p=0.001) and fallers (r= 0.54; p=0.03). There was a moderate negative correlation (r= -0.52; p=0.03) between FES-I-Brazil and gait cadence in fallers. There was a greater presence of stairs (p=0.001) and throw rugs (p=0.03) in the homes of fallers than non-fallers. Conclusion: The elderly women were not sarcopenic. Elderly fallers presented inferior gait cadence and a greater fear of falling. Residential risks were determining factors for falls, and were more relevant than intrinsic factors in the evaluation of falls among active community-dwelling elders.